Total Quality Management and Managerial Performance: The Role of Innovation Performance and Budget Participation as Moderating Variables - Yunita Christy; Se Tin; Anthonius (International Journal of Social Science and Business, 2023)
Management accounting systems can be used as an organizational control mechanism and an effective tool for managers to control their activities and reduce environmental uncertainty in order to achieve organizational goals successfully. The aim of this research is to analyze the influence of TQM on managerial performance and on managerial performance when moderated by innovation performance and budget participation. The type of research used in this research is quantitative research using survey methods. The population in this study were employees from several companies operating in the customer goods sector. The sample in this research was selected using a purposive sampling method which is non-probability sampling where the sample is selected according to criteria so that it can support the research. The criteria for this sampling are managers or heads at manager level who have been involved in the budget preparation process. The research method used in this article is moderation regression analysis. The findings in this research show that TQM has a positive effect on managerial performance, the same results when innovation performance becomes a moderating variable on the relationship between TQM and managerial performance, while budget participation cannot moderate the relationship between TQM and managerial performance. This research has the implication that up to now TQM can still effectively improve managerial performance in a company, especially when strengthened by the strength of human resources in following technological developments, the desire to innovate.